Design space exploration through liquid H2 tank preliminary sizing and design of experiments analysis - Mazzoni, Filippo; Biga, Roberta; Manrique-Escobar, Camilo Andrés; Brusa, Eugenio; Delprete, Cristiana (International journal of hydrogen energy, 2024)
Energy transition towards renewable sources is essential to reduce the use of fossil fuels. To link sources and final users a flexible, available, and scalable solution must be found. Hydrogen represents the best choice being, by definition, an excellent energy carrier. The present work focuses on the aviation sector. Storage volume, critical temperature and pressure conditions, hydrogen embrittlement and boil-off phenomena are just a few of the many challenges in the design of a hybrid aircraft. The proposed analysis consists of a preliminary sizing model for a liquid hydrogen tank followed by a full-factorial design of experiments analysis. The aim of this study is to explore the design space, identifying which are the most relevant aspects, prioritizing the design parameters, and investigating their effects. These goals are reached by analyzing the quantitative data coming produced the form of chart, tables, and interaction plots. Results and observations can be useful tools to guide the engineers in understanding which areas of study are worth of greater efforts. [Display omitted] •Identification of the main challenges of liquid hydrogen storage for aviation.•Tank preliminary design for gravimetric and volumetric indexes evaluation.•Hydrogen tank preliminary sizing for airborne applications.•Quantification of the influence of key design parameters and noise factors.